A Practice-Based Professional Development Program to Support Scientific Argumentation From Evidence in the Elementary Classroom. Issue 3 (3rd April 2017) - Fishman, Evan J.; Borko, Hilda; Osborne, Jonathan; Gomez, Florencia; Rafanelli, Stephanie; Reigh, Emily; Tseng, Anita; Million, Susan; Berson, Eric
ABSTRACT: Considerable evidence suggests that dialogical interaction in the classroom promotes students' scientific knowledge building and reasoning. Hence, scientific argumentation is recognized as a central component of the Next Generation Science Standards. A focus on argumentation, however, requires teachers to adopt instructional practices that facilitate this type of discourse. Therefore, the study reported here examined the impact of a practice-based professional development (PD) program on the scientific discourse practices of teachers and their students. Two cohorts of elementary school teachers attended different versions of the PD: 1 cohort attended the full program (institute, practicum, and follow-up sessions), whereas the other took part in the institute and follow-up days but did not take part in the practicum. We found that all teachers and their students, regardless of the cohort, made statistically significant improvements in their science discourse practices after attending the PD. An unexpected finding was that teachers who attended the full PD (with practicum) did not outperform the teachers who did not attend the practicum. However, students of teachers who did attend the practicum made improvements that approached statistical significance compared to students of teachers who did not attend the practicum. Thus, we report research that provides evidence of an effective model of practice-based PD that helps teachers to address the goals of the Next Generation Science Standards and equips them with instructional practices that promote student learning in science.